2023
DOI: 10.3390/molecules28145420
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-Flavonoids in Nature: A Critical Review of Structural Diversity and Bioactivity

Abstract: Based on the literature data from 1973 to 2022, this work summarizes reports on spiro-flavonoids with a spiro-carbon at the center of their structure and how this affects their isolation methods, stereochemistry, and biological activity. The review collects 65 unique structures, including spiro-biflavonoids, spiro-triflavonoids, spiro-tetraflavonoids, spiro-flavostilbenoids, and scillascillin-type homoisoflavonoids. Scillascillin-type homoisoflavonoids comprise spiro[bicyclo[4.2.0]octane-7,3′-chromane]-1(6),2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Spirocycles are ubiquitous in natural products, synthetic drugs and functional materials. 89 Because of their attractive biological profile, the stereoselective synthesis of spiro compounds has long been pursued by chemists. 90 The synthesis of chiral multi-substituted 3H-spiro[benzofuran-2,1 0 -cyclopentane] 89 from readily accessible benzoquinones 86 and allylic alcohols 87 was reported by Wang et al 91 The catalysis system Cu(II)/BOX was found to be suitable to generate intermediate 88, which upon treatment with Lewis acid SnCl 4 provided final spiro products 89.…”
Section: Synthesis Of Spiro Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirocycles are ubiquitous in natural products, synthetic drugs and functional materials. 89 Because of their attractive biological profile, the stereoselective synthesis of spiro compounds has long been pursued by chemists. 90 The synthesis of chiral multi-substituted 3H-spiro[benzofuran-2,1 0 -cyclopentane] 89 from readily accessible benzoquinones 86 and allylic alcohols 87 was reported by Wang et al 91 The catalysis system Cu(II)/BOX was found to be suitable to generate intermediate 88, which upon treatment with Lewis acid SnCl 4 provided final spiro products 89.…”
Section: Synthesis Of Spiro Frameworkmentioning
confidence: 99%
“…Spirocycles are ubiquitous in natural products, synthetic drugs and functional materials. 89 Because of their attractive biological profile, the stereoselective synthesis of spiro compounds has long been pursued by chemists. 90…”
Section: Synthesis Of Spiro Frameworkmentioning
confidence: 99%
“…Chromane is a bicyclic scaffold, ubiquitous in a wide variety of bioactive natural products and synthetic compounds exhibiting antitumor, anti-inflammatory, antiviral, antiprotozoal, and antimicrobial effects [1][2][3][4][5][6][7][8][9][10]. Among them, some have also shown moderate-to-good antitubercular activities [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%